Jasser Auda’s System Approach in The Rules of Marriage Dispensation in Indonesia (Review of Maqashid Syariah) - Wardatun Nabilah; Dewi Putri; Deri Rizal (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This article discusses the view of maqashid sharia with the theory of the Jasser Auda system approach to the implementation of the rules regarding marriage dispensation that apply in Indonesia. CATAHU (Annual Notes) Komnas Perempuan in 2020 notes that the dispensation of marriage (child marriage) is another thing that has an extreme threefold increase based on BADILAG data, namely from 23,126 cases in 2019, a sharp increase of 64,211 cases in 2020. This is because among others, of a pandemic situation such as the intensity of the use of gadgets and family economic problems as well as the amendment to the Marriage Law which increases the age of marriage to 19 years for women. The research method used is qualitative research methods, with the type of library research, data collection techniques through observation of secondary and primary data. Based on the results of the research conducted by the author, it can be concluded that the rules regarding the granting of permission for marriage compensation need to be reviewed so that it does not appear to facilitate the legalization of marriage, especially for child marriage.